Functional characterization of the Cydia pomonella granulovirus matrix metalloprotease - Ishimwe, Egide (Kansas State University, 2014)
Cydia pomonella granulovirus (CpGV) is a member of the Baculoviridae family of viruses. The CpGV open reading frame 46 (CpGV-ORF46) predicts a 545 amino acid protein that shares homology with matrix metalloproteases (MMPs), a family of zinc-dependent endopeptidases that degrade extracellular matrix proteins. In silico analyses revealed the presence of putative mmp genes in all species from the Betabaculovirus genus, while no mmps were identified in members of the Alphabaculovirus, Gammabaculovirus or Deltabaculovirus genera. Unlike most cellular MMPs, baculovirus MMPs do not have a propeptide domain, a domain involved in regulating MMP activation, or a hemopexin-like domain, which is necessary for substrate binding and specificity in many MMPs. However, Betabaculovirus MMPs do contain a predicted conserved zinc-binding motif (HEXGHXXGXXHS/T) within their catalytic domain. The function of CpGV-MMP and its effects on baculovirus replication in cultured cells and insect larvae were investigated. CpGV-MMP was expressed in and purified from Escherichia coli, and activity was measured using a generic MMP substrate in vitro. CpGV-MMP had in vitro activity and its activity was specifically inhibited by MMP inhibitors. To study the effects of CpGV-MMP on virus replication and dissemination, CpGV-MMP was expressed from Autographa californica nucleopolyhedrovirus (AcMNPV) under the control of a strong and constitutive promoter, the Drosophila heat shock 70 protein promoter. Expression of CpGV-MMP did not affect virus replication in cultured cells. The effects of expressing CpGV-MMP from AcMNPV during larval infection were evaluated in the presence or absence of the AcMNPV chitinase and cathepsin genes. Insect bioassays showed that the absence of cathepsin resulted in a significant delay in larval time of death; however, this delay was compensated by expression of CpGV-MMP. In addition, larval time of death was accelerated when cathepsin, chitinase, and CpGV-MMP were all expressed. Finally, we determined the effects of CpGV-MMP on larvae melanization and liquefaction. CpGV-MMP was able to promote larvae melanization in the absence of cathepsin. CpGV-MMP, in the absence of cathepsin, was not able to promote larvae liquefaction. When chitinase was engineered to be secreted from cells, CpGV-MMP rescued liquefaction in the absence of cathepsin. In conclusion, CpGV-MMP is a functional MMP which can enhance larvae mortality with the presence of cathepsin. In addition, CpGV-MMP can promote larvae melanization; however, it can only promote liquefaction when chitinase is engineered to be secreted from cells.
Keywords: Virology; Baculovirus; Matrix metalloproteases; Cathepsin; Chitinase; Biology (0306); Virology (0720)